2011
DOI: 10.1021/ol103173v
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis of 5H-Cyclopenta[c]quinoline Derivatives via Palladium-Catalyzed Domino Reactions of o-Alkynylhalobenzene with Amine

Abstract: A novel and efficient route for the synthesis of 5H-cyclopenta[c]quinoline derivatives via a palladium-catalyzed domino reaction of o-alkynylhalobenzene with amine is described. The starting materials are easily available, and the reaction proceeds smoothly with high efficiency, which shows broad scope with good functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Different imidazolium ionic liquids were also tested, and [BMIm]Br appeared to be the best solvent for this transformation (entry 3 vs. 5-9). Acidic ionic liquids, such as [BMIm][HSO 4 ], or acidic catalysts, for example, TsOH and AgOTf, were used to further improve the yields of the product 4a, to our disappointed, the results are not good (Table 1, entries [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different imidazolium ionic liquids were also tested, and [BMIm]Br appeared to be the best solvent for this transformation (entry 3 vs. 5-9). Acidic ionic liquids, such as [BMIm][HSO 4 ], or acidic catalysts, for example, TsOH and AgOTf, were used to further improve the yields of the product 4a, to our disappointed, the results are not good (Table 1, entries [10][11][12].…”
Section: Resultsmentioning
confidence: 99%
“…The United States government-sponsored clinical trials for antimalarial drug development showed unequivocally that chloroquine has a significant therapeutic value as an antimalarial drug. Accordingly, novel strategies for the synthesis of quinolines continued to receive considerable attention in the field of organic synthetics chemistry [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…19 When the reaction was performed in the presence of palladium(II) acetate (5 mol%), tricyclohexylphosphine (10 mol%), and potassium tert-butoxide in refluxing 1,4-dioxane, the indene-containing polycycle 38 was obtained in 85% yield. Mechanistic studies showed that this novel pathway involves a double carbopalladation.…”
Section: Palladium-catalyzed Reactions Of 1-alkynyl-2-bromobenzenesmentioning
confidence: 99%
“…After two hours the required N-nucleophile was added along with additional base, resulting in the desired aryl amination followed by ring closure. [20] Scheme 7. Access to further heterocyclic derivatives such as 7-azaindoles and thienopyrroles can also be accomplished by use of the corresponding ortho-alkynylhalopyridine or orthoalkynylhalothiophene substrates, respectively.…”
Section: C-n Bond Formationmentioning
confidence: 99%